Prevalence and predictors of ventricular remodeling after anterior myocardial infarction in the era of modern medical therapy - Farah, Elaine [UNESP]; Cogni, Ana Lucia [UNESP]; Minicucci, Marcos Ferreira [UNESP]; Gaiolla, Paula Schmidt Azevedo [UNESP]; Okoshi, Katashi [UNESP]; Matsubara, Beatriz Bojikian [UNESP]; Zanati, Silmeia G. [UNESP]; Haggeman, Rodrigo [UNESP]; Paiva, Sergio Alberto Rupp de [UNESP]; Zornoff, Leonardo Antonio Mamede [UNESP] (Int Scientific Literature, Inc, 2012)
Background: The consequences of aggressive therapy following a myocardial infarction (MI) on ventricular remodeling are not well established. Thus, the objective of this study was to analyze the prevalence, clinical characteristics, and predictors of left ventricular remodeling in the era of modern medical therapy.Material/Methods: Clinical characteristics and echocardiographic data were analyzed in 66 consecutive patients with anterior infarction at admission and at 6-month follow-up. Ventricular remodeling was defined as an increase of 10% in ventricular end-systolic or end-diastolic diameter.Results: In our study, 58% of patients presented with ventricular remodeling. Patients with remodeling possessed higher total plasma creatine kinase (CPK), MB-fraction (CPK-MB), heart rate, heart failure, shortness of breath, and reperfusion therapy than patients without remodeling. In contrast, patients with remodeling had a smaller ejection fraction, E-Wave deceleration time (EDT), and early (E' Wave) and late (A' Wave) diastolic mitral annulus velocity (average of septal and lateral walls), but a higher E/E' than patients without remodeling. Patients with remodeling used more diuretics, digoxin, oral anticoagulants and aldosterone antagonists than patients without remodeling. In the multivariate analyses, only E' Wave was an independent predictor of ventricular remodeling. Each 1 unit increase in the E' Wave was associated with a 59% increased odds of ventricular remodeling.Conclusions: In patients with anterior MI, despite contemporary treatment, ventricular remodeling is still a common event. In addition, diastolic function can have an important role as a predictor of remodeling in this scenario.
Keywords: predictors; remodeling; ventricular dilation